STRATEGI KEPALA MADRASAH DALAM MENGELOLA TRANSISI PEMBELAJARAN MENUJU DEEP LEARNING DI MADRASAH IBTIDAIYAH PADA ERA KURIKULUM MERDEKA - Rofii’atul Fitriyyah (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
The implementation of the Merdeka Curriculum in Indonesia demands a fundamental paradigm shift in teaching and learning at Madrasah Ibtidaiyah (MI), transitioning from surface-level instruction toward Deep Learning that cultivates six global competencies (6Cs): Character, Citizenship, Collaboration, Communication, Creativity, and Critical Thinking. This study investigates the strategies employed by MI principals in orchestrating this pedagogical transition within the Merdeka Curriculum framework. Employing a qualitative case study design (Yin, 2018), research was conducted at two Madrasah Ibtidaiyah in West Java Province, Indonesia. Data were gathered through semi-structured interviews with eight participants comprising principals, vice principals, and classroom teachers, supplemented by direct classroom observation and document review. Thematic analysis (Braun & Clarke, 2022) generated findings across three principal strategy domains: (1) cultivating collaborative professional learning communities; (2) strengthening teachers' Deep Learning pedagogical competencies integrated with Islamic values; and (3) restructuring learning environments to foster student agency. The findings affirm that effective Deep Learning transition in MI requires transformational leadership that is instructionally grounded, islamically informed, and responsively adaptive to the socio-cultural context of Indonesian Islamic primary education.